STRUCTURATION IN COMMUNICATION OF VEGETABLE FARMERS WITH MIDDLEMAN IN BATURITI DISTRICT TABANAN BALI - Siringo Ringo, Renata Lusilaora; Darma Putra, I Nyoman; Sutrisno, Nanang; Banda, Maria Matildis (E-Journal of Cultural Studies; Vol 17 No 1 (2024): Volume 17 Number 1 February 2024, 2024)
This study aimed to uncover patterns of structuration in communication between vegetable growers and intermediaries in the Baturiti District. This study employs a critical communication methodology. Data was gathered via interviews, observations, and document analysis approaches. Data analysis was conducted using descriptive qualitative interactive methods based on structuration theory. Phatic communication, patron-client relations, and divergent communication are forms of structuration in communication, as revealed by the research results. According to the empirical findings in this research, communication actions are shown to improve relationships, resulting in a tendency towards greater intimacy. The result is that the relationship pattern of vegetable farmers has been tied to economic actors, namely middlemen, for a very long time. The theoretical finding in this research is that structuration in communication is in line with the concept of symbolic interactionism, which focuses on efforts to provide interactions using symbols and containing power to weak parties. This research contributes to policy making related to the use of agricultural products. Keywords: communication structuration, vegetable farmers, middlemen